DIPLOMASI DIGITAL INDONESIA SEBAGAI ALAT PROMOSI PARIWISATA RAJA AMPAT - Suryanti, Made Selly Dwi; Sinaga, Melpayanty (Indonesian Journal of International Relations, 2023)
This research describes Indonesia's position in promoting Raja Ampat tourism by using soft power in the form of digital diplomacy. For this reason, a qualitative method was used with an online interview approach and using the conceptual framework of digital diplomacy and tourism. The results of this study indicate that digital diplomacy regarding Raja Ampat's tourism potential is carried out using the branding "Wonderful Indonesia", and "Pesona Indonesia" digitally through the websites and also through several social media platforms (Facebook and Instagram). It was found that there were several obstacles that needed to get the relevant Government's attention. namely, the limited funds faced by Raja Ampat management to manage the website, the limited resources in operating the website, and the limited staff involved in promoting Raja Ampat to international exhibitions. This research can be used as study material for policy makers to help promote tourism through digital diplomacy and can be used as a model for future research.